Electromagnetic Fields on Time-Involute Particles Around Biharmonic Particles and its Lorentz Transformations in Heisenberg Spacetime - Korpinar, Talat; Asil, Vedat; Turhan, Essin (Springer/Plenum Publishers, 2015)
In this paper, we obtain the new parametric representation for a time-involute particles in Heisenberg spacetime . By using the Frenet frame, we derive the necessary and sufficient conditions to construct a biharmonic particle Heisenberg spacetime . We give a geometrical description of time-involute particles around timelike biharmonic particle in . Moreover, we obtain Lorentz transformations this particles. Finally, we give the relationship of electromagnetic fields on Heisenberg spacetime.
Keywords: Energy; Bienergy; Heisenberg group; Faraday tensor; Involute particle; Lorentz transformations